2021
DOI: 10.1088/1755-1315/905/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of brand switching of milk product for young children aged 1-3 years in consumers of middle to lower socioeconomic class in urban communities in malang

Abstract: A total of 56.7% of Indonesia’s population today is concentrated in urban areas. More than 80% of Indonesians belong to the middle and lower socioeconomic class and this segment is the biggest consumer of milk products for young children aged 1-3 years called growing-up milk (GUM). Understanding the brand and customer behaviour is significantly important. This study aimed to examine the behavior of GUM brand switching on middle to lower socioeconomic class consumers in urban communities. The research was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The decision to switch from one brand to another is a dynamic and multifaceted process involving several behavioral factors [ 41 ]. A consumer's reluctance to switch brands as a result of positive prior brand-purchasing experiences [ 19 ]. Without adequate product attributes, consumers may switch brands [ 42 ].…”
Section: Review Of Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…The decision to switch from one brand to another is a dynamic and multifaceted process involving several behavioral factors [ 41 ]. A consumer's reluctance to switch brands as a result of positive prior brand-purchasing experiences [ 19 ]. Without adequate product attributes, consumers may switch brands [ 42 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…[ 47 , 48 ] revealed that when previous purchases produced negative results, consumers switched to other brands of products. Furthermore [ [17] , [18] , [19] ], discovered that bad previous purchasing experiences will drive consumers to switch brands. However, according to Ref.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations